(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
Currently, new waste management technologies are being introduced. To date, a number of measures and activities are being developed aimed at improving the living conditions of the population and preventing environmental pollution.The article also introduces current issues, i.e. new biological methods of waste treatment, technologies for the use of plants are being introduced. The cleanup is expected to have no negative impact on the environment and to achieve greater economic efficiency.